Collagen and chitosan membranes from alternative sources: evaluation of their potential for Tissue Engineering applications - Castro-Piedra, Silvia E. (2015)
Natural polymers such as collagen and chitosan possess physical, chemical and biological characteristics that make them good candidates as extracellular matrix scaffolds with potential applications in Tissue Engineering. In the present work, collagen and chitosan biopolymer membranes made from waste material, were evaluated for dermal fibroblasts cell culture. Several membrane compositions were analyzed, including 100% collagen, 100% chitosan, 8:2, 2:8, 6:4, 4:6 collagen-chitosan, obtained from alternative sources (shrimp shells and fish scales). Given that sterilization is one of the main challenges for using materials and devices in biomedicine, we evaluated different methods to achieve this, including chemical (ethanol, antibiotics and acetone) and physical (X-rays, UVC irradiation) treatments. Antibiotic and antifungal immersion for 48 hours was the only procedure that allowed complete sterilization without compromising the integrity of the membranes. Also, we were able to confirm cellular adhesion and proliferation on the membranes. These results demonstrate the potential of these materials to be used as scaffolds in Tissue Engineering applications.